Oliceridine (TRV130), a Novel G Protein–Biased Ligand at the μ‐Opioid Receptor, Demonstrates a Predictable Relationship Between Plasma Concentrations and Pain Relief. I: Development of a Pharmacokinetic/Pharmacodynamic Model. (7th February 2018) - Fossler, Michael J.; Sadler, Brian M.; Farrell, Colm; Burt, David A.; Pitsiu, Maria; Skobieranda, Franck; Soergel, David G.
Abstract: Conventional opioids bind to μ‐opioid receptors and activate 2 downstream signaling pathways: G‐protein coupling, linked to analgesia, and β‐arrestin recruitment, linked to opioid‐related adverse effects and limiting efficacy. Oliceridine (TRV130) is a novel G protein–biased ligand at the μ‐opioid receptor that differentially activates G‐protein coupling while mitigating β‐arrestin recruitment. Using data derived from both phase 1 studies in healthy volunteers as well as data from a phase 2 study examining the efficacy of oliceridine for the treatment of postbunionectomy pain, we have developed a population pharmacokinetic/pharmacodynamic model linking the pharmacokinetics of oliceridine to its effect on pain, as measured by the Numeric Pain Rating Scale score. Phase 1 data consisted of 145 subjects (88% male, 12% female), who received single doses of oliceridine ranging between 0.15 and 7 mg, as well as multiple doses ranging from 0.4 to 4.5 mg every 4–6 hours. Sixteen of these subjects were CYP2D6 poor metabolizers, who have lower oliceridine clearance than extensive metabolizers. Approximately 265 subjects (10% male, 90% female) came from the phase 2 study, in which they received active doses ranging from 0.5 to 4 mg every 3–4 hours. The final model was a 3‐compartment model that included covariates of body weight, sex, and CYP2D6 status. The PD model was an indirect response model linked to plasma oliceridine concentrations and included the placebo pain response over the 48‐hour treatment period. The EC50 for oliceridine on pain relief was estimated as 10.1 ng/mL (95%CI, 8.4–12.1 ng/mL). Model qualification showed that the model robustly reproduced the original data.